Development Of An Avirulent Pasteurella Multocida B:2 By Disruption Of The Aba392 Dna Fragment - Mohamed Zulperi, Dzarifah (2008)

(untitled)
Haemorrhagic septicaemia (HS) is an acute disease infecting cattle and buffaloes caused by Pasteurella multocida serotype B:2 which leads to great economic losses in countries with expanded animal industries such as Malaysia. This study was conducted to construct a mutant derived from the 921bp ABA392 virulence gene in order to make avirulent P. multocida serotype B:2, thus making this P. multocida B:2 mutant a potential candidate for a live-attenuated vaccine against HS. The detection of a fragment which is related to P. multocida B:2 pathogenicity, the 921bp ABA392 virulence gene was carried out using Polymerase Chain Reaction (PCR) assay. Two P. multocida isolates, namely PMTB and 3030, isolated from a HS outbreak were used for PCR amplification. The particular 921bp DNA fragment was found to be present in P. multocida B:2 genome as 803bp in size. Sequencing of the recombinant plasmids confirmed that the 803bp gene was 98% homologous to the reference sequence, the virulence 921bp ABA392 DNA fragment.Southern hybridization analysis revealed the 804bp of ABA392 gene was located at approximately 6kb position in the P. multocida B:2 genome. PCR performed towards the approximately 6kb DNA fragment produced an 803bp band which was confirmed to be the ABA392 virulence gene. The amplified PCR product was cloned and sequenced. Nucleotide sequences obtained were 98% identical to the reference strain, the 921bp ABA392 virulence gene. Pathogenicity test on the recombinant plasmids proved that the 804bp gene inserted within these plasmids still possessed the virulence properties of the 921bp ABA392 gene which may lead to HS disease in cattle and buffaloes. In an attempt to produce P. multocida B:2 mutants through allelic exchange, the 804bp of ABA392 gene which was disrupted with kanamycin cassette was cloned inside suicide plasmid pAKA19 through shotgun ligation technique. The desired 7kb product was transformed into several different E. coli (TOP 10, JM109, AS11Yλ and DH5α) hosts for preservation. Verification of the 7kb ligation product with digestion by PstI, HindIII and XhoI restriction enzymes revealed the exact sizes of kanamycin cassette (1.2kb), pAKA19 (5.0kb) and the disrupted 804bp of ABA392 virulence gene (804bp). An antibiotic sensitivity test on P. multocida B:2 and the respective E. coli strains were performed in order to select the donor and recipient strains for conjugation process. This test revealed that E. coli DH5α was suitable for the donor strain since it showed low resistance to streptomycin and P. multocida B:2 as the recipient strain for its high resistance towards streptomycin. Conjugation between donor and recipient strains was then achieved by plate-mating method. About 20 single colonies of positive transconjugants were picked and subcultured on BHI blood agar containing kanamycin for 5 days to encourage loss of pAKA19 plasmid and to enhance the allelic exchange between the ABA392::KmR insert with the native ABA392 gene on the recipient chromosome. No plasmid was observed which indicated the loss of suicide plasmid. Direct colony PCR was performed to detect the changes in the ABA392 gene of the parent strain, where a 2kb band was observed signifying that allelic exchange has taken place and the organism is now a P. multocida B:2 mutants. Parent strains of P. multocida B:2 were highly virulent and killed mice within 24 hours. Mice inoculated with P. multocida B:2 mutant survived. Direct smear from mice’s heart blood inoculated with the mutant showed the existence of bipolar organism which indicated the presence of P. multocida B:2. This result firmly suggests that the mutant, named as PMTBK was greatly attenuated and is thus a potential candidate organism for a live attenuated vaccine against HS.